Coating material and preparation method thereof, coated modified positive electrode material and preparation method thereof, battery

By using lithium-modified composite material of sodium feldspar and carbon nanotubes to coat the cathode material, the problem of prone to rupture and side reactions during the circulation process is solved, and the circulation performance and life of the battery are significantly improved.

CN119390141BActive Publication Date: 2025-03-25ZHUJI PAWA NEW ENERGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411981941.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The positive electrode material is prone to rupture during the circulation process, and there are continuous side reactions with the electrolyte, which seriously damages the cycle life and rate performance of the battery.

Method used

A composite material of lithium modified sodium feldspar and carbon nanotubes was used as the cladding material, and a coating modified cathode material was prepared by mixing the precursor of the cathode material with the cladding material and performing presintering and sintering treatment.

Benefits of technology

Through coating modification, the cycling performance of the battery is improved, side reactions are reduced, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390141B_ABST
    Figure CN119390141B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery materials, and discloses a coating material and a preparation method thereof. A silicon source solution is added dropwise to a mixed solution of an aluminum source and a sodium source, and the pH value of the system is stirred and adjusted to 9-11; after the silicon source solution is added, a lithium source is added to obtain a mixed material; the mixed material is reacted at 110-200°C, and after the reaction is completed, lithium-modified sodium feldspar is obtained; the lithium-modified sodium feldspar is mixed with carbon nanotubes and heat-treated under an inert atmosphere to obtain a composite material of lithium-modified sodium feldspar and carbon nanotubes, i.e., a coating material. The positive electrode material coated and modified by the coating material can improve the cycle performance of the battery. The present invention also discloses a precursor coated and modified by the coating material, a positive electrode material, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a coating material and a preparation method thereof, as well as a coated modified positive electrode material and a preparation method thereof, and a battery. Background Art

[0002] The long driving range and fast charging of electric vehicles require high-performance lithium-ion batteries to achieve, and the positive electrode material is one of the most important components. However, the positive electrode material is easy to break during the cycle, and there are continuous side reactions with the electrolyte, which seriously damages the cycle life and rate performance of the battery. Surface coating can reduce stress, increase the wettability of the liquid electrolyte, reduce the interfacial charge transfer resistance, and reduce side reactions, thereby effectively optimizing the positive electrode material. CN115954464A discloses a high-nickel positive electrode material coated with a gap-type oxygen ion conductor and a preparation method thereof, which uses a high-nickel positive electrode material precursor, a lithium source and a dopant as raw materials, mixes them evenly, and calcines them in an oxygen-rich atmosphere to obtain a doped high-nickel positive electrode material; uses a doped high-nickel positive electrode material and nano-gap oxygen ion conductor particles as raw materials, mixes them evenly, and calcines them to obtain a doped high-nickel positive electrode material coated with a gap-type oxygen ion conductor. CN113363450A discloses a method for preparing a carbon nanotube-coated high-nickel ternary positive electrode composite material, comprising the following steps: S1, using biomass as a raw material to prepare a carbon source; S2, preparing a mixed solution of dicyandiamide and nickel nitrate, adding the carbon source to the mixed solution, and calcining the mixed solution mixed with the carbon source at high temperature to prepare bamboo-shaped carbon nanotubes; S3, mixing the bamboo-shaped carbon nanotubes with a high-nickel ternary material, and transferring the mixed powder to a grinding device for crushing and grinding to prepare a carbon nanotube-coated high-nickel ternary positive electrode composite material. For a long time, the best surface coating material and coating method have been the focus of research. Summary of the invention

[0003] The first object of the present invention is to provide a coating material and a method for preparing the same.

[0004] The second object of the present invention is to provide a coated modified positive electrode material and a preparation method thereof.

[0005] A third object of the present invention is to provide a battery.

[0006] To achieve the above objectives, the present invention provides the following specific technical solutions.

[0007] First, the present invention provides a method for preparing a coating material, comprising:

[0008] Add the silicon source solution dropwise into the mixed solution of the aluminum source and the sodium source, stir and adjust the pH value of the system to 9-11;

[0009] After the silicon source solution is added, the lithium source is added to obtain a mixed material;

[0010] The mixed material is reacted at 110-200°C, and after the reaction is completed, lithium-modified albite is obtained;

[0011] After the lithium-modified albite and the carbon nanotubes are mixed, heat treatment is performed at 500-1000° C. in an inert atmosphere to obtain a composite material of the lithium-modified albite and the carbon nanotubes, namely, a coating material.

[0012] In a further preferred embodiment, the aluminum source is at least one of aluminum chloride and aluminum sulfate; the sodium source is at least one of sodium hydroxide and sodium carbonate; and the silicon source is sodium silicate.

[0013] In a further preferred embodiment, the concentration of Al in the mixed solution is 0.01-0.2 mol / L, the concentration of Na is 0.01-0.2 mol / L; the concentration of Si in the silicon source solution is 0.03-0.6 mol / L.

[0014] In a further preferred embodiment, the amounts of the mixed solution, silicon source solution and lithium source are determined according to the molar ratio of n(Al):n(Na):n(Si):n(Li)=0.5~2:0.5~2:0.3~6:0.05~1.

[0015] In a further preferred embodiment, the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium chloride, lithium sulfate, lithium acetate and lithium fluoride.

[0016] In a further preferred embodiment, the mass ratio of lithium-modified albite to carbon nanotubes is 1:0.02-1.

[0017] In a further preferred embodiment, the inert atmosphere includes at least one of argon and nitrogen.

[0018] Based on the same inventive concept, the present invention provides a coating material prepared by the above preparation method.

[0019] In addition, the present invention provides a coated and modified positive electrode material, comprising the aforementioned coating material.

[0020] Furthermore, the present invention provides a method for preparing a coated modified positive electrode material, comprising:

[0021] The precursor of the positive electrode material and the aforementioned coating material are mixed, and then pre-sintered to obtain a pre-sintered product;

[0022] The pre-sintered product is mixed with lithium salt and then sintered.

[0023] In a further preferred embodiment, the precursor of the positive electrode material is a ternary precursor. The chemical formula of the ternary precursor is Ni x Co y Mn z (OH)2, where 0.6≤x<1, 0<y≤0.3, 0<z≤0.3, x+y+z =1.

[0024] In a further preferred embodiment, the pre-sintering temperature is 150-500° C., and the pre-sintering time is 1-8 hours.

[0025] In a further preferred embodiment, the sintering temperature is 600-1200° C., and the sintering time is 5-30 hours.

[0026] In a further preferred embodiment, the mass ratio of the precursor of the positive electrode material to the coating material is 1:0.001-0.05.

[0027] The present invention further provides a battery, comprising a coated modified positive electrode material.

[0028] Compared with the prior art, the above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects:

[0029] The present invention proposes a new coating material.

[0030] The process for preparing the coating material of the present invention is simple, the operation is controllable, and large-scale production is possible.

[0031] The positive electrode material modified by coating with the coating material of the present invention can improve the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the XRD pattern of the lithium-modified feldspar composite carbon nanotubes prepared in Example 1.

[0033] Figure 2 This is the SEM image of the coated and modified positive electrode material obtained in Example 1.

[0034] Figure 3 This is the SEM image of the positive electrode material obtained in Comparative Example 5.

[0035] Figure 4 The cycle performance diagram of the battery assembled with the positive electrode materials obtained in Example 1 and Comparative Examples 1 to 5.

[0036] Figure 5 This is a cycle performance diagram of a battery assembled with the positive electrode materials obtained in Examples 2 to 6. DETAILED DESCRIPTION

[0037] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0038] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0040] Example 1

[0041] Step S1: Preparation of lithium-modified albite

[0042] Aluminum chloride and sodium hydroxide were added into water to prepare a mixed solution with Al concentration of 0.1 mol / L and Na concentration of 0.1 mol / L.

[0043] Sodium silicate was dissolved in water to prepare a silicon source solution with a Si concentration of 0.6 mol / L.

[0044] 50 mL of silicon source solution was added dropwise into 100 mL of the mixed solution, and the pH value of the system was adjusted to 10±0.5.

[0045] After the silicon source solution was added, 0.005 mol of lithium carbonate was added to obtain a mixed material.

[0046] The mixture was transferred into a high pressure reactor and reacted at 160°C for 12 h.

[0047] After the reaction is completed, the reaction product is naturally cooled to room temperature, centrifuged and filtered, and the solid phase is washed with water and dried to obtain lithium-modified albite.

[0048] Step S2: Preparation of lithium-modified albite composite carbon nanotubes

[0049] Lithium-modified albite and carbon nanotubes were mixed in a mass ratio of 1:0.1, then put into a ball mill, and ball-milled at a rotation speed of 400 rpm for 4 hours to obtain a ball-milled material.

[0050] The ball mill was transferred to a tube furnace, heated at 800° C. in a nitrogen atmosphere and kept warm for 2 h, and then naturally cooled to room temperature to obtain lithium-modified albite composite carbon nanotubes. Figure 1 This is the XRD pattern of lithium-modified albite composite carbon nanotubes.

[0051] Step S3: Preparation of coated modified positive electrode material

[0052] The nickel-cobalt-manganese ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and lithium-modified albite composite carbon nanotubes were mixed in a mass ratio of 1:0.01, pre-sintered at 250°C for 3 hours, and then mixed with lithium hydroxide in a molar ratio of 1:1.05 and sintered at 850°C in an air atmosphere for 22 hours to obtain a coated modified positive electrode material.

[0053] Figure 2 This is the SEM image of the coated and modified positive electrode material obtained in Example 1.

[0054] Comparative Example 1

[0055] Step S1: Preparation of albite

[0056] Aluminum chloride and sodium hydroxide were added into water to prepare a mixed solution with Al concentration of 0.1 mol / L and Na concentration of 0.1 mol / L.

[0057] Sodium silicate was dissolved in water to prepare a silicon source solution with a Si concentration of 0.6 mol / L.

[0058] 50 mL of silicon source solution was added dropwise into 100 mL of the mixed solution, and the pH value of the system was adjusted to 10±0.5.

[0059] After the silicon source solution is added, a mixed material is obtained.

[0060] The mixture was transferred into a high pressure reactor and reacted at 160°C for 12 h.

[0061] After the reaction is completed, the reaction product is naturally cooled to room temperature, centrifuged and filtered, and the solid phase is washed with water and dried to obtain albite.

[0062] Step S2: Preparation of albite composite carbon nanotubes

[0063] Sodium feldspar and carbon nanotubes were mixed in a mass ratio of 1:0.1, then put into a ball mill, and ball-milled at a rotation speed of 400 rpm for 4 hours to obtain a ball-milled material.

[0064] The ball abrasive was transferred to a tubular furnace, heated at 800° C. and kept warm for 2 h in a nitrogen atmosphere, and then naturally cooled to room temperature to obtain albite composite carbon nanotubes.

[0065] Step S3: Preparation of coated modified positive electrode material

[0066] The nickel-cobalt-manganese ternary precursor Ni 0.9 Co 0.05 Mn 0.05(OH)2 and albite composite carbon nanotubes were mixed in a mass ratio of 1:0.01, pre-sintered at 250°C for 3 hours, and then mixed with lithium hydroxide in a molar ratio of 1:1.05 and sintered at 850°C in an air atmosphere for 22 hours to obtain a coated modified positive electrode material.

[0067] Comparative Example 2

[0068] Step S1: Preparation of lithium-modified albite

[0069] Aluminum chloride and sodium hydroxide were added into water to prepare a mixed solution with Al concentration of 0.1 mol / L and Na concentration of 0.1 mol / L.

[0070] Sodium silicate was dissolved in water to prepare a silicon source solution with a Si concentration of 0.6 mol / L.

[0071] 50 mL of silicon source solution was added dropwise into 100 mL of the mixed solution, and the pH value of the system was adjusted to 10±0.5.

[0072] After the silicon source solution was added, 0.005 mol of lithium carbonate was added to obtain a mixed material.

[0073] The mixture was transferred into a high pressure reactor and reacted at 160°C for 12 h.

[0074] After the reaction is completed, the reaction product is naturally cooled to room temperature, centrifuged and filtered, and the solid phase is washed with water and dried to obtain lithium-modified albite.

[0075] Step S2: Preparation of coated modified positive electrode material

[0076] The nickel-cobalt-manganese ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 was mixed with lithium-modified albite in a mass ratio of 1:0.1, pre-sintered at 250°C for 3 hours, and then mixed with lithium hydroxide in a molar ratio of 1:1.05 and sintered at 850°C in an air atmosphere for 22 hours to obtain a coated modified positive electrode material.

[0077] Comparative Example 3

[0078] Step S1: Preparation of albite

[0079] Aluminum chloride and sodium hydroxide were added into water to prepare a mixed solution with Al concentration of 0.1 mol / L and Na concentration of 0.1 mol / L.

[0080] Sodium silicate was dissolved in water to prepare a silicon source solution with a Si concentration of 0.6 mol / L.

[0081] 50 mL of silicon source solution was added dropwise into 100 mL of the mixed solution, and the pH value of the system was adjusted to 10±0.5 with stirring.

[0082] After the silicon source solution is added, a mixed material is obtained.

[0083] The mixture was transferred into a high pressure reactor and reacted at 160°C for 12 h.

[0084] After the reaction is completed, the reaction product is naturally cooled to room temperature, centrifuged and filtered, and the solid phase is washed with water and dried to obtain albite.

[0085] Step S2: Preparation of coated modified positive electrode material

[0086] The nickel-cobalt-manganese ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and albite were mixed in a mass ratio of 1:0.01, pre-sintered at 250°C for 3 hours, and then mixed with lithium hydroxide in a molar ratio of 1:1.05 and sintered at 850°C in an air atmosphere for 22 hours to obtain a coated modified positive electrode material.

[0087] Comparative Example 4

[0088] The nickel-cobalt-manganese ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 was mixed with carbon nanotubes in a mass ratio of 1:0.01, pre-sintered at 250°C for 3 hours, and then mixed with lithium hydroxide in a molar ratio of 1:1.05 and sintered at 850°C in an air atmosphere for 22 hours to obtain a coated modified positive electrode material.

[0089] Comparative Example 5

[0090] The nickel-cobalt-manganese ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and lithium hydroxide were mixed in a molar ratio of 1:1.05 and sintered at 850°C in an air atmosphere for 22 hours to obtain a positive electrode material. Figure 3 is the SEM image of the obtained positive electrode material.

[0091] Example 2

[0092] Step S1: Preparation of lithium-modified albite

[0093] Aluminum chloride and sodium hydroxide were added into water to prepare a mixed solution with Al concentration of 0.01 mol / L and Na concentration of 0.01 mol / L.

[0094] Sodium silicate was dissolved in water to prepare a silicon source solution with a Si concentration of 0.03 mol / L.

[0095] 100 mL of silicon source solution was added dropwise into 100 mL of the mixed solution, and the pH value of the system was adjusted to 11 with stirring.

[0096] After the silicon source solution was added, 0.001 mol of lithium carbonate was added to obtain a mixed material.

[0097] The mixture was transferred to a high pressure reactor and reacted at 200°C for 1 h.

[0098] After the reaction is completed, the reaction product is naturally cooled to room temperature, centrifuged and filtered, and the solid phase is washed with water and dried to obtain lithium-modified albite.

[0099] Step S2: Preparation of lithium-modified albite composite carbon nanotubes

[0100] Lithium-modified albite and carbon nanotubes were mixed in a mass ratio of 1:0.02, and then put into a ball mill and ball-milled at a rotation speed of 400 rpm for 4 hours to obtain a ball-milled material.

[0101] The ball mill was transferred to a tube furnace, heated at 500° C. and kept warm for 1 h under a nitrogen atmosphere, and then naturally cooled to room temperature to obtain lithium-modified albite composite carbon nanotubes.

[0102] Step S3: Preparation of coated modified positive electrode material

[0103] The nickel-cobalt-manganese ternary precursor Ni 0.6 Co 0.2 Mn 0.2 (OH)2 and lithium-modified albite composite carbon nanotubes were mixed in a mass ratio of 1:0.02, pre-sintered at 250°C for 3 hours, and then mixed with lithium hydroxide in a molar ratio of 1:1.05 and sintered at 600°C in an air atmosphere for 30 hours to obtain a coated modified positive electrode material.

[0104] Example 3

[0105] Step S1: Preparation of lithium-modified albite

[0106] Aluminum chloride and sodium hydroxide were added into water to prepare a mixed solution with Al concentration of 0.2 mol / L and Na concentration of 0.2 mol / L.

[0107] Sodium silicate was dissolved in water to prepare a silicon source solution with a Si concentration of 0.4 mol / L.

[0108] 100 mL of silicon source solution was added dropwise into 100 mL of the mixed solution, and the pH value of the system was adjusted to 10.5.

[0109] After the silicon source solution was added, 0.004 mol of lithium carbonate was added to obtain a mixed material.

[0110] The mixture was transferred into a high pressure reactor and reacted at 150°C for 3 h.

[0111] After the reaction is completed, the reaction product is naturally cooled to room temperature, centrifuged and filtered, and the solid phase is washed with water and dried to obtain lithium-modified albite.

[0112] Step S2: Preparation of lithium-modified albite composite carbon nanotubes

[0113] Lithium-modified albite and carbon nanotubes were mixed in a mass ratio of 1:1, then put into a ball mill, and ball-milled at a rotation speed of 400 rpm for 4 hours to obtain a ball-milled material.

[0114] The ball mill was transferred to a tube furnace, heated at 600° C. and kept warm for 2 h in a nitrogen atmosphere, and then naturally cooled to room temperature to obtain lithium-modified albite composite carbon nanotubes.

[0115] Step S3: Preparation of coated modified positive electrode material

[0116] The nickel-cobalt-manganese ternary precursor Ni 0.7 Co 0.1 Mn 0.2 (OH)2 and lithium-modified albite composite carbon nanotubes were mixed in a mass ratio of 1:0.001, pre-sintered at 500°C for 1 hour, and then mixed with lithium hydroxide in a molar ratio of 1:1.05 and sintered at 1200°C in an air atmosphere for 5 hours to obtain a coated modified positive electrode material.

[0117] Example 4

[0118] Step S1: Preparation of lithium-modified albite

[0119] Aluminum chloride and sodium hydroxide were added into water to prepare a mixed solution with Al concentration of 0.15 mol / L and Na concentration of 0.15 mol / L.

[0120] Sodium silicate was dissolved in water to prepare a silicon source solution with a Si concentration of 0.3 mol / L.

[0121] 100 mL of silicon source solution was added dropwise into 100 mL of the mixed solution, and the pH value of the system was adjusted to 9 with stirring.

[0122] After the silicon source solution was added, 0.1 mol of lithium carbonate was added to obtain a mixed material.

[0123] The mixture was transferred to a high pressure reactor and reacted at 130°C for 2 h.

[0124] After the reaction is completed, the reaction product is naturally cooled to room temperature, centrifuged and filtered, and the solid phase is washed with water and dried to obtain lithium-modified albite.

[0125] Step S2: Preparation of lithium-modified albite composite carbon nanotubes

[0126] Lithium-modified albite and carbon nanotubes were mixed in a mass ratio of 1:0.5, and then put into a ball mill and ball-milled at a rotation speed of 400 rpm for 4 hours to obtain a ball-milled material.

[0127] The ball mill was transferred to a tube furnace, heated at 800° C. in a nitrogen atmosphere and kept warm for 2 h, and then naturally cooled to room temperature to obtain lithium-modified albite composite carbon nanotubes.

[0128] Step S3: Preparation of coated modified positive electrode material

[0129] The nickel-cobalt-manganese ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium-modified albite composite carbon nanotubes were mixed in a mass ratio of 1:0.05, pre-sintered at 350°C for 2h, and then mixed with lithium hydroxide in a molar ratio of 1:1.05 and sintered at 900°C in an air atmosphere for 22.5h to obtain a coated modified positive electrode material.

[0130] Example 5

[0131] Step S1: Preparation of lithium-modified albite

[0132] Aluminum chloride and sodium hydroxide were added into water to prepare a mixed solution with Al concentration of 0.05 mol / L and Na concentration of 0.05 mol / L.

[0133] Sodium silicate was dissolved in water to prepare a silicon source solution with a Si concentration of 0.1 mol / L.

[0134] 50 mL of the silicon source solution was added dropwise into 100 mL of the mixed solution, and the pH value of the system was adjusted to 10.5 with stirring.

[0135] After the silicon source solution was added, 0.001 mol of lithium carbonate was added to obtain a mixed material.

[0136] The mixture was transferred into a high pressure reactor and reacted at 110°C for 2 h.

[0137] After the reaction is completed, the reaction product is naturally cooled to room temperature, centrifuged and filtered, and the solid phase is washed with water and dried to obtain lithium-modified albite.

[0138] Step S2: Preparation of lithium-modified albite composite carbon nanotubes

[0139] Lithium-modified albite and carbon nanotubes were mixed in a mass ratio of 1:0.6, and then put into a ball mill and ball-milled at a rotation speed of 400 rpm for 4 hours to obtain a ball-milled material.

[0140] The ball mill was transferred to a tube furnace, heated at 900° C. in a nitrogen atmosphere and kept warm for 2 h, and then naturally cooled to room temperature to obtain lithium-modified albite composite carbon nanotubes.

[0141] Step S3: Preparation of coated modified positive electrode material

[0142] The nickel-cobalt-manganese ternary precursor Ni 0.7 Co 0.2 Mn 0.1 (OH)2 and lithium-modified albite composite carbon nanotubes were mixed in a mass ratio of 1:0.005, pre-sintered at 150°C for 8 hours, and then mixed with lithium hydroxide in a molar ratio of 1:1.05 and sintered at 900°C in an air atmosphere for 24 hours to obtain a coated modified positive electrode material.

[0143] Example 6

[0144] Step S1: Preparation of lithium-modified albite

[0145] Aluminum chloride and sodium hydroxide were added into water to prepare a mixed solution with Al concentration of 0.1 mol / L and Na concentration of 0.1 mol / L.

[0146] Sodium silicate was dissolved in water to prepare a silicon source solution with a Si concentration of 0.3 mol / L.

[0147] 100 mL of silicon source solution was added dropwise into 100 mL of the mixed solution, and the pH value of the system was adjusted to 9.5.

[0148] After the silicon source solution was added, 0.005 mol of lithium carbonate was added to obtain a mixed material.

[0149] The mixture was transferred to a high pressure reactor and reacted at 160°C for 2 h.

[0150] After the reaction is completed, the reaction product is naturally cooled to room temperature, centrifuged and filtered, and the solid phase is washed with water and dried to obtain lithium-modified albite.

[0151] Step S2: Preparation of lithium-modified albite composite carbon nanotubes

[0152] Lithium-modified albite and carbon nanotubes were mixed in a mass ratio of 1:0.09, and then put into a ball mill and ball-milled at a rotation speed of 400 rpm for 2 hours to obtain a ball-milled material.

[0153] The ball mill was transferred to a tube furnace, heated at 1000° C. in a nitrogen atmosphere and kept warm for 2 h, and then naturally cooled to room temperature to obtain lithium-modified albite composite carbon nanotubes.

[0154] Step S3: Preparation of coated modified positive electrode material

[0155] The nickel-cobalt-manganese ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and lithium-modified albite composite carbon nanotubes were mixed in a mass ratio of 1:0.01, pre-sintered at 225°C for 4 hours, and then mixed with lithium hydroxide in a molar ratio of 1:1.05 and sintered at 750°C in an air atmosphere for 18 hours to obtain a coated modified positive electrode material.

[0156] The positive electrode materials obtained in Examples 1-6 and Comparative Examples 1-5 were respectively assembled into batteries in the following manner: the positive electrode material, Super-P, KS-6 and polyvinylidene fluoride (PVDF) were mixed in N-methyl-2-pyrrolidone (NMP) at a mass ratio of 89:5:3.5:2.5 to prepare a uniform positive electrode slurry. The prepared positive electrode slurry was evenly coated on aluminum foil, and a fast coating machine was used to ensure uniform coating, and then dried under a vacuum environment of 120°C for 2 hours to ensure that NMP was completely volatilized and a dry positive electrode material layer was obtained to obtain a positive electrode sheet. The positive electrode sheet was cut into a disc (12 mm diameter) suitable for a button battery. A metal lithium sheet was selected as the negative electrode, a Celgard-2400 diaphragm was selected as the diaphragm, a solution of 1M LiPF6 dissolved in EC+DMC+EMC (volume ratio 1:1:1) was used as the electrolyte, and aluminum foil was used as the positive electrode current collector.

[0157] Place the negative electrode shell on the assembly table; place the metal lithium negative electrode sheet into the negative electrode shell; place the Celgard-2400 diaphragm on the negative electrode sheet to ensure tight coverage; drip an appropriate amount of electrolyte on the diaphragm to ensure that the diaphragm and the negative electrode sheet are fully soaked; place the dried positive electrode sheet on top of the diaphragm; drip a small amount of electrolyte on the positive electrode sheet; place the metal gasket and spring sheet in order to ensure close contact inside; place the positive electrode shell on the top; use a button battery packaging machine for packaging to ensure that the battery is sealed to avoid electrolyte leakage.

[0158] The battery cycle performance was tested at 25°C, with an operating voltage range of 3.0-4.3 V, 2 cycles at 0.1C, and then 100 cycles at 0.5C.

[0159] Test results such as Figure 4~Figure 5 As shown. Figure 4 It can be seen from the figure that the present invention can improve the cycle performance of the battery by coating and modifying the positive electrode material with lithium-modified sodium feldspar and carbon nanotube coating materials. Figure 5 It can be seen that the battery assembled with the coated modified positive electrode material has good cycle performance.

[0160] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a coating material, characterized in that: include: Add the silicon source solution dropwise into the mixed solution of the aluminum source and the sodium source, stir and adjust the pH value of the system to 9-11; After the silicon source solution is added, the lithium source is added to obtain a mixed material; The mixed material is reacted at 110-200°C, and after the reaction is completed, lithium-modified albite is obtained; After the lithium-modified albite and the carbon nanotubes are mixed, heat treatment is performed at 500-1000° C. in an inert atmosphere to obtain a composite material of the lithium-modified albite and the carbon nanotubes, namely, a coating material.

2. The method for preparing the coating material according to claim 1, characterized in that: The aluminum source is at least one of aluminum chloride and aluminum sulfate; the sodium source is at least one of sodium hydroxide and sodium carbonate; the silicon source is sodium silicate; and the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium chloride, lithium sulfate, lithium acetate, and lithium fluoride.

3. The method for preparing the coating material according to claim 1, characterized in that: The concentration of Al in the mixed solution is 0.01-0.2 mol / L, and the concentration of Na is 0.01-0.2 mol / L; the concentration of Si in the silicon source solution is 0.03-0.6 mol / L.

4. The method for preparing a coating material according to any one of claims 1 to 3, characterized in that: The amounts of the mixed solution, silicon source solution and lithium source are determined according to the molar ratio n(Al):n(Na):n(Si):n(Li)=0.5~2:0.5~2:0.3~6:0.05~1.

5. The method for preparing the coating material according to claim 1, characterized in that: The mass ratio of lithium-modified albite to carbon nanotubes is 1:0.02~1.

6. A coating material, characterized in that: The coating material is prepared by the method for preparing the coating material according to any one of claims 1 to 5.

7. A coated modified positive electrode material, characterized in that: Comprising the coating material as described in claim 6.

8. A method for preparing a coated modified positive electrode material, characterized in that: include: Mixing a precursor of a positive electrode material and the coating material according to claim 6, and then pre-sintering to obtain a pre-sintered product; The pre-sintered product is mixed with lithium salt and then sintered.

9. The preparation method according to claim 8, characterized in that: Include at least one of the following conditions (1) to (4): (1) The precursor of the positive electrode material is a ternary precursor; (2) The pre-sintering temperature is 150-500°C, and the pre-sintering time is 1-8 hours; (3) The sintering temperature is 600-1200°C and the sintering time is 5-30h; (4) The mass ratio of the precursor to the coating material is 1:0.001~0.

05.

10. A battery, characterized in that: It includes the coated and modified positive electrode material according to claim 7 or the coated and modified positive electrode material prepared by the preparation method according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Preparation method of carbon nanotube coated high-nickel ternary positive electrode composite material

    CN113363450A

  • Gap-type oxygen ion conductor coated high-nickel positive electrode material and preparation method thereof

    CN115954464A

  • Preparation method of lithium ferric phosphate / grapheme composite positive electrode material

    CN102169986A

  • Method for preparing sodium alumino silicate through decomposing feldspar

    CN103818914A